MISSING/missing - Ong, Danilo B., Jr. (Animo Repository, 2022)
Grief and mourning are both seen as stages towards processing the death of a loved one. As these two processes are emotional responses, the death of a loved one cannot be fully fathomed from the perspective of the abstract; however, photography can be used as a tool to translate the feelings expounded by grief and mourning. This study aims to expound on the abstraction of grief and mourning through narrative storytelling with the use of conceptual photography, musical composition, and archived family footage. The study aimed to understand grief and mourning through the medium of conceptual photography interconnected with archived family photographs from the narrative of the researcher that will be complemented by his own family on the experience of loss through multimedia photography essay which can be viewed on missingmissing.net.